The dilemma in energy transition in Malaysia: A comparative life cycle assessment of large scale solar and biodiesel production from palm oil. (20th May 2022) - Phuang, Zhen Xin; Lin, Zuchao; Liew, Peng Yen; Hanafiah, Marlia Mohd; Woon, Kok Sin
Abstract: Energy transition to renewable energy is a current global trend. Being the world's second-largest palm oil and third-largest solar photovoltaic cells producer, Malaysia prioritizes palm biodiesel as biofuel and large scale solar as renewable energy sources. Nevertheless, disputed issues such as land occupation and embodied environmental impacts of both technologies are not backed with data-driven evaluation from a life cycle perspective. This study compares the environmental impacts and identifies the environmental hotspots of palm biodiesel and large scale solar systems using life cycle assessment methodology under the same system boundary and functional unit (i.e., 1 MJ of energy). There are 18 impact categories and three damage assessments evaluated with ReCiPe 2016 via SimaPro 9.1. The large scale solar systems perform more favorably than palm biodiesel systems by 77% in all damage assessments. The environmental hotspots in palm biodiesel (i.e., fresh fruit bunch production and milling) and large scale solar systems (i.e., electrical installation) show environmental burdens up to 15–51% in human non-carcinogenic toxicity, human carcinogenic toxicity, global warming, marine ecotoxicity, water consumption, and fossil resource scarcity. Anthropogenic carbon dioxide emissions from fossil fuel usage and land transformation in palm biodiesel systems are of positive value when compared (i.e., 11 g CO2 /MJ PB) to large scale solar systems. The aluminum recycling in large scale solar systems and anaerobic digestion biogas plant in the palm biodiesel system can reduce the environmental impact between 4.13% and 25%. Policy implications are recommended for policymakers for better decision-making aligned with the national renewable energy implementation road map. Graphical abstract: Image 1 Highlights: Comparative life cycle analysis of palm biodiesel and large scale solar is studied. Large scale solar shows 77% less environmental burden than palm biodiesel. Fresh fruit bunch production and milling stages cause 81–89% environmental burden. Electrical installation in large scale solar causes 36–38% environmental burden. This study provides data-driven evaluation to energy policy and land transformation.